Repetitive Negative Thinking in Anticipation of a Stressor - McEvoy, Peter; Moulds, M.; Mahoney, A. (Australian Academic Press Pty Ltd, 2014)
Repetitive negative thinking (RNT) has been confirmed as a transdiagnostic phenomenon, but most measures of RNT are contaminated with diagnosis-specific content. The first aim of this study was to examine the structure of an anticipatory version of the Repetitive Thinking Questionnaire (RTQ-Ant) as a trans-emotional measure of anticipatory RNT. The original RTQ was completed with reference to a past stressor, whereas the RTQ-Ant instructs respondents to link their responses to a future stressor. The second aim was to test if the associations between a range of emotions (anxiety, depression, shame, anger, general distress) and the original post-stressor version of the RTQ would be replicated. Undergraduates (N = 175, 61% women) completed the RTQ-Ant, along with measures of various emotions, with reference to upcoming university exams. Principal axis factor analysis yielded many similarities between the original post-event RTQ and the RTQ-Ant, and some differences. The RTQ-Ant was comprised of two subscales: the RNT subscale measures engagement in repetitive thinking, negative thoughts about oneself, and ‘why’ questions; and the Isolated Contemplation (IC) subscale included items referring to isolating oneself and reflecting on negative thoughts, feelings, loneliness, and listening to sad music. RNT was more strongly related to negative emotions than IC. The RTQ-Ant appears to be a reliable measure of anticipatory RNT that is associated with a broad array of emotions.